Effects of Quality of Administrative Services and Quality of Health Services on Patient Satisfaction in Tanjung Redeb Health Center, Berau Regency - Eka Iriana Wijayanti; Syachrumsyah Asri; Suroyo Suroyo (International Journal of Community Service & Engagement, 2022)
This research was driven by patient satisfaction survey data at the Tanjung Redeb Public Health Center (Pukesmas), Berau Regency which provided input and advice on service quality, where administrative services and services were provided by health workers (medical and paramedical). The existence of dissatisfaction on the part of the patient, triggers the authors to investigate the quality of administrative services and the quality of health care services on patient satisfaction simultaneously. The objectivity of the sample was outpatients at the Tanjung Redeb Puskesmas (Berau Regency). The correlational quantitative approach and accidental sampling technique invited 100 respondents to be interviewed. Collecting data using a questionnaire with a Likert scale. Through multiple linear regression analysis, it shows that there is a positive and significant effect between the quality of administrative services and the quality of health care services on the level of patient satisfaction. The research output also stimulates the improvement of professional service quality. Future research directions need to consider other aspects beyond the factors that influence patient satisfaction other than the level of service.